2001
DOI: 10.14214/sf.590
|View full text |Cite
|
Sign up to set email alerts
|

Effects of wood ash fertilization on forest soil chemical properties

Abstract: The effects of wood ash fertilization on soil chemical properties were studied in three young Scots pine (Pinus sylvestris L.) plantations and a Norway spruce (Picea abies (L.) Karst.) plantation with different site fertility in southern Finland. The dose of 3 t ha -1 of loose wood ash was applied to 4 replicate plots (25 × 25 m) at each experiment. Humus layer and mineral soil samples were taken before the treatment and 7 and 16 years after wood ash application. Results showed that neutralization as well as f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
71
2
6

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(95 citation statements)
references
References 13 publications
14
71
2
6
Order By: Relevance
“…The objectives of our work were to evaluate the P fertilizing effect of biomass ashes on different soils, and to investigate possible interactions between the effects of ashes and cultivated crops. (Jamil et al 2004) 0.01 Alfalfa stem ash (Mozaffari et al 2002) 0.90 Horticulture ashes (Zhang et al 2002) 0.04-1.00 Wood ashes (Erich and Ohno 1992;Saarsalmi et al 2001;Hyt€ onen 2003) 0.90-1.70 Wheat straw ash (Hyt€ onen 2003) 1.30 Rape straw ash (Hyt€ onen 2003) 2.10 Poultry litter ash (Yusiharni 2001;Codling et al 2002) 5.00 Cereal ash (Eichler et al 2008b) 10.4…”
Section: Introductionmentioning
confidence: 99%
“…The objectives of our work were to evaluate the P fertilizing effect of biomass ashes on different soils, and to investigate possible interactions between the effects of ashes and cultivated crops. (Jamil et al 2004) 0.01 Alfalfa stem ash (Mozaffari et al 2002) 0.90 Horticulture ashes (Zhang et al 2002) 0.04-1.00 Wood ashes (Erich and Ohno 1992;Saarsalmi et al 2001;Hyt€ onen 2003) 0.90-1.70 Wheat straw ash (Hyt€ onen 2003) 1.30 Rape straw ash (Hyt€ onen 2003) 2.10 Poultry litter ash (Yusiharni 2001;Codling et al 2002) 5.00 Cereal ash (Eichler et al 2008b) 10.4…”
Section: Introductionmentioning
confidence: 99%
“…Patterson et al (2004) found a total P concentration of 0.6% in wood waste ash (wood, bark, and knots). In investigations by Erich and Ohno (1992), Saarsalmi et al (2001), and Hytönen (2003) wood ashes contained 0.9-1.7% P. In general, hardwood ash has more P than ash of softwood (Pitman 2006). P concentrations of more than 1% were detected in peat ash (1.3%, Hytönen 2003), in saw dust ash (1.3%, Awodun 2007), and in different straw ashes: wheat straw ash (1.3%), barley straw ash (1.7%), rye straw ash (1.6%), and rape straw ash (2.1%) (Sander and Andrén 1997).…”
Section: Introductionmentioning
confidence: 99%
“…While Saarsalmi et al [14] observed an increase in concentration of almost all nutrients except N in soil amended with wood ash. Though wood ash amendment in mineral soils was found not to have any positive growth response in plants growing on such soils [13] [15].…”
Section: /19mentioning
confidence: 91%
“…Though wood ash amendment in mineral soils was found not to have any positive growth response in plants growing on such soils [13] [15]. Enriching the soil with wood ash would cause some changes in the metabolism and physiological activity of plants [14] [16] and soil properties. The capacity of the soils to retain and release heavy metals can be an important factor to predict environmental impact of the use of wastes or residues containing these metals.…”
Section: /19mentioning
confidence: 99%